(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
By the anthropological and sociological point of view ‘identity’ is correlated with status, age, sex, family, profession and nationality. Loss of spiritualism and bonding with materialism are the two polarities in which every human is caught and suspended. This paper is the study of the crux of women characters between social responsibility and desired self.